Search for spatial correlations of Neutrinos with Ultra-high-energy Cosmic Rays - The ANTARES collaboration (2022)
Fil: Fil: Binet, V. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Física de Rosario (IFIR-CONICET); Argentina.